2013
DOI: 10.1111/pce.12129
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition of transpiration and rates of change in leaf water isotopologue storage in response to environmental variables

Abstract: During daylight hours, the isotope composition of leaf water generally approximates steady-state leaf water isotope enrichment model predictions. However, until very recently there was little direct confirmation that isotopic steady-state (ISS) transpiration in fact exists. Using isotope ratio infrared spectroscopy (IRIS) and leaf gas exchange systems we evaluated the isotope composition of transpiration and the rate of change in leaf water isotopologue storage (isostorage) when leaves were exposed to variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 56 publications
5
121
0
Order By: Relevance
“…Leaves remained in the chamber for 30-60 min, and measurements over the final 20 min were averaged. The inlets to the photosynthesis systems were connected to a vaporization module to provide a CO 2 -free air stream with constant vapour concentration and d 18 O, as described by Simonin et al (2013). The mass flow controllers within the vaporization module were set to deliver a minimum of 2.5 l min À1 flow, to provide sufficient flow to supply both photosynthesis systems and the water vapour laser.…”
Section: Leaf Anatomymentioning
confidence: 99%
See 2 more Smart Citations
“…Leaves remained in the chamber for 30-60 min, and measurements over the final 20 min were averaged. The inlets to the photosynthesis systems were connected to a vaporization module to provide a CO 2 -free air stream with constant vapour concentration and d 18 O, as described by Simonin et al (2013). The mass flow controllers within the vaporization module were set to deliver a minimum of 2.5 l min À1 flow, to provide sufficient flow to supply both photosynthesis systems and the water vapour laser.…”
Section: Leaf Anatomymentioning
confidence: 99%
“…The stable oxygen isotope composition of water vapour was measured using a Cavity Ring-Down Spectrometer (L1102-i; Picarro Inc., Sunnyvale, CA, USA), as described by Simonin et al (2013). The L1102-i was calibrated using two standard water samples (d 18 O À14.93 and À0.95&, relative to VSMOW, measured using a stable isotope mass spectrometer at The Australian National University, Canberra, Australia) that spanned the range in d…”
Section: Coupled Gas Exchange and Isoflux Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Only when transpiration is in isotopic steady state is its isotopic composition equal to that of xylem water, which integrates all water sources taken up by a plant. Recent studies applying laser spectroscopy showed that the measured isotopic composition of transpiration often deviated from isotopic steady state and that, especially in a highly variable environment, long leaf water turnover times might prevent isotopic steady-state transpiration (Simonin et al, 2013;Dubbert et al, 2014;Song et al, 2015). To test for potential deviations from isotopic steady state, we performed a preliminary experiment with the same experimental set-up as described above.…”
Section: In Situ Isotope Monitoringmentioning
confidence: 99%
“…The short leaf water residence times, calculated according to Farquhar & Cernusak (2005) and amounting on average to c. 25 min for oak and c. 20 min for beech between 09:00 h and 19:00 h, might have favored isotopic steady state in transpiration under these conditions. We acknowledge that step changes in environmental conditions as applied by Simonin et al (2013) and long residence times of leaf water of > 5 h as determined by Dubbert et al (2014) might be more problematic with our approach. In general, closed static chamber systems might inherently cause errors in isotope measurements as a result of nonsteady operating conditions (Ohlsson et al, 2005;Yepez et al, 2005).…”
Section: And Dmentioning
confidence: 99%